Pemberdayaan Masyarakat Lingkar Tambang dengan Sistem Food Gardening Dalam Mendukung Ketahananan Pangan Desa Pesouha Kabupaten Kolaka - Marlina Mustafa; Yolanda Fitria Syahri; Masitah Masitah; Fahruddin Fahruddin; Yunus Musa; Muhammad Arsyad (Universitas Muhammadiyah Sidenreng Rappang, 2024)
Food gardening is an alternative to meet the food and nutritional needs of the family. Empowerment the community in the nickel mining area of Pesouha Village, Kolaka Regency is carried out using the DFT hydroponic system with the aim of ensuring adequate family food through PKK groups in degraded environments. Community empowerment is carried out in 4 stages, namely (1) socialization stage (2) training stage (3) product packaging stage and (4) monitoring and evaluation stage. The results obtained from this community empowerment activity are that the PKK group partners of Pesouha Village have understood, have the ability and infrastructure for hydroponic planting in their yards